Seroprevalence of TORCH antibody in pregnant women - Nabi, SN; Wasey, AFSA; Haider, KMTS; Khan, AA; Hoque, MM (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13537 JAFMC Vol.8(1) 2012 pp.35-39